Needlescopic herniorrhaphy using one umbilical 5-mm trocar and two lateral 3-mm trocars: A case series. (2018) - Imagami, Toru; Takayama, Satoru
Highlights: Needlescopic transabdominal preperitoneal repair using one 5-mm instrument and two 3-mm instruments are extremely rare. We performed needlescopic herniorrhaphy using one umbilical 5-mm trocar and two lateral 3-mm trocars for seven patients. Needlescopic herniorrhaphy is minimally invasive herniorrhaphy than conventional methods. Abstract: Introduction: Laparoscopic surgery has become a standard treatment for inguinal hernia, with it recently being characterized by the use of smaller instruments. However, reports on needlescopic transabdominal preperitoneal repair using one umbilical 5-mm and two lateral 3-mm trocars are extremely rare. Methods: Seven patients with unilateral inguinal hernia underwent this surgical procedure. A 5-mm trocar was inserted from the umbilical and two 3-mm trocars were inserted from the lateral. After dissection of the preperitoneal layer, a mesh was fixed using a tucker inserted from the umbilical 5-mm trocar while viewing through the 3-mm optics from the lateral trocar. Results: All procedures were completed without intraoperative complications and conversion to the conventional method. The surgical results of our needlescopic TAPP repair have been shown to not be inferior to those of the conventional method. Conclusion: Our needlescopic herniorrhaphy using one umbilical 5-mm trocar and two lateral 3-mm trocars is minimally invasive hernia repair.